2010
DOI: 10.1093/tropej/fmp143
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Profile of Term Appropriate for Gestational Age Neonates in Nigeria: A Forerunner to Screening for Congenital Hypothyroidism

Abstract: Thyroid hormones in normal quantity are vital for physical growth and mental development during fetal and postnatal life. The available publications in Sub-Saharan Africa on the thyroid function of newborn infants was reported in babies delivered in moderate to severe goitre zones; utilizing the hormone levels from these studies may have a measure of bias. Newborn screening for congenital hypothyroidism (CH) in Sub-Saharan Africa is still a mirage, the technicality of the best timing for collection of blood sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 13 publications
7
13
1
Order By: Relevance
“…This may result in more severe reduction in the iodine content in the newborn thyroid and consequently reduction in its functional capacities. The demonstrated pattern of postnatal changes at 72hours in this study (higher mean T 3 , T 4 and lower TSH) compared with mean cord blood levels is similar to that reported in Benin 15 . This suggest that the postnatal changes in neonatal thyroid function are qualitatively the same irrespective of geographical location but there may be slight quantitative differences.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This may result in more severe reduction in the iodine content in the newborn thyroid and consequently reduction in its functional capacities. The demonstrated pattern of postnatal changes at 72hours in this study (higher mean T 3 , T 4 and lower TSH) compared with mean cord blood levels is similar to that reported in Benin 15 . This suggest that the postnatal changes in neonatal thyroid function are qualitatively the same irrespective of geographical location but there may be slight quantitative differences.…”
Section: Discussionsupporting
confidence: 87%
“…Coincidentally a similar method of assay was used (ELISA technique), though the test kits were different. The Benin study 15 showed lower mean serum T 4 and higher mean serum T 3 and TSH than this present study. This observation may be due to the differences in location, Sokoto being a mild goiter zone while Benin is in an area of moderate goiter.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…[12][13][14][15][16] According to research in the world, the prevalence of congenital hypothyroidism varied from 0.14 per 1,000 live births in Japan to 14.7 per 1,000 infants in Nigeria which lower than the present study. 7,17,18 The causes of the different prevalence of the disease in different parts of the world can be due to the different contraceptive criteria for the diagnosis of hypothyroidism, use of T4 or TSH to screen, iodine deficiency in some parts of the world, the percentage of different marriages and ethnic and racial differences. [19][20][21][22][23][24][25] In this study, the rate of recall was 5600 cases or 35 cases per 1000 (3.5%) infants.…”
Section: Discussionmentioning
confidence: 99%